Crescimento, trocas gasosas e teores foliares de nutrientes em plantas de Coffea arabica L. tratadas com reguladores de crescimento - Erlacher, Wellington Abeldt (2017)
The present study aimed to evaluate the effect of 3-Indoleacetic acid (IAA) and kinetinon the growth, gas exchange and leaf nutrient content in coffee plants (Coffea arabicaL.). Two experiments were carried out; the first one with IAA application and the